Evaluación de las estrategias de vinculación con la colectividad y de práctica profesional de la carrera de Jurisprudencia de la Universidad Técnica de Machala, mediante el funcionamiento de los consultorios jurídicos gratuitos en la ciudad de Machala, provincia de el oro, periodo 2012- 2013, y propuesta de un plan estratégico de formación y potenciación - Barzola Castro, Alcides Roberto (2014)
The development of this thesis entitled "EVALUATION OF STRATEGIES OF RELATIONSHIP WITH THE COMMUNITY OF PRACTICE AND PROFESSIONAL CAREER OF JURISPRUDENCE OF THE TECHNICAL UNIVERSITY OF MACHALA, BY OPERATION OF FREE LEGAL CLINICS IN THE CITY OF MACHALA, PROVINCE OF THE ORO, 2012- 2013 PERIOD, AND PROPOSAL OF A STRATEGIC PLAN FOR TRAINING AND EMPOWERMENT " it is part of a problem which corresponds to the Accreditation and Categorizing institutions of higher education, while including aspects related to the development of legal clinics free career Jurisprudence, Faculty of Social Sciences at the Technical University of Machala, as a strategy of linking the university with the most vulnerable sectors of society that require access to justice. The aim of the research was aimed at determining the level of linking strategies with the community and professional practice of career Jurisprudence UTMACH by the operation of free legal clinics in the city of Machala.